Laparoscopic appendectomy in surgical treatment of acute appendicitis - G. I. Ohrimenko; N. G. Golovko; V. A. Grushka; D. A. Detsyk; Ye. I. Haidarzhi; A. A. Podluzhniy; Ya. V. Terelya (Zaporožskij Medicinskij Žurnal)
Relevance of the topic. At the present time laparoscopic appendectomy has taken its own place at the urgent surgery. In spite of this less is studied in the field of the use of the minimally invasive technologies in the cases of complicated acute appendicitis.